Optimization of Mechanical Properties of Raw Agave Fibre-Reinforced Lightweight Foamed Concrete - Mydin, Md Azree Othuman; Abdullah, M.M. Al Bakri; Omar, R.; Dulaimi, A.; Wan Ibrahim, W.M.; Jeż, B.; Nabiałek, M. (2024)
The utilization of readily accessible natural fibres in lightweight foamed concrete (LWFC), which is already a widely used building material, can have a substantial positive impact on the environment. Therefore, the mechanical characteristics might be increased by using a correct mix proportion of fibre-reinforced LWFC. Innovative LWFC-agave fibre (AF) composites were created in this experiment. In order to get the best mechanical qualities, this investigation set out to establish the correct weight fraction of AF to be added to LWFC. Two LWFC densities of 750 and 1500 kg/m3 were produced with the addition of several weight fractions of AF, precisely 0.0%, 1.5%, 3.0%, 4.5%, 6.0%, and 7.5%, were used. To establish the mechanical characteristics of LWFCAF composites, flexural tests, tensile strength tests, axial compression tests, and ultrasonic pulse velocity tests were carried out. Test results revealed that the combination of LWFC together with a weight fraction of 4.5% of AF exhibited superior mechanical properties. Beyond 4.5% of AF’s weight fraction, the mechanical properties started to deteriorate. This study gives insight and crucial data on the mechanical characteristics of LWFC-AF composites therefore it will enable future researchers to explore other properties of LWFC reinforced with AF.